Dioxygen Binding in the Active Site of Histone Demethylase JMJD2A and the Role of the Protein Environment - Cortopassi, Wilian A; Simion, Robert; Honsby, Charles E; França, Tanos C C; Paton, Robert S (Chemistry (Weinheim an der Bergstrasse, Germany), 2015)
JMJD2A catalyses the demethylation of di- and trimethylated lysine residues in histone tails and is a target for the development of new anticancer medicines. Mechanistic details of demethylation are yet to be elucidated and are important for the understanding of epigenetic processes. We have evaluated the initial step of histone demethylation by JMJD2A and demonstrate the dramatic effect of the protein environment upon oxygen binding using quantum mechanics/molecular mechanics (QM/MM) calculations. The changes in electronic structure have been studied for possible spin states and different conformations of O2 , using a combination of quantum and classical simulations. O2 binding to this histone demethylase is computed to occur preferentially as an end-on superoxo radical bound to a high-spin ferric centre, yielding an overall quintet ground state. The favourability of binding is strongly influenced by the surrounding protein: we have quantified this effect using an energy decomposition scheme into electrostatic and dispersion contributions. His182 and the methylated lysine assist while Glu184 and the oxoglutarate cofactor are deleterious for O2 binding. Charge separation in the superoxo-intermediate benefits from the electrostatic stabilization provided by the surrounding residues, stabilizing the binding process significantly. This work demonstrates the importance of the extended protein environment in oxygen binding, and the role of energy decomposition in understanding the physical origin of binding/recognition.
Keywords: Protein Binding; JMJD2A; doména Jumonji s histondemethylasami; Histone Demethylases; chemical biology; histondemethylasy; epigenetics; histone demethylation; Jumonji Domain-Containing Histone Demethylases; QM/MM calculations; vazebná místa; histony; Histones; Binding Sites; vazba proteinů